Close-coupling calculations of positronium formation in positron-helium scattering - Chaudhuri, P.; Adhikari, S. K. (Iop Publishing Ltd, 1998)
Positronium (Ps) formation in positron-helium scattering has been investigated in different partial waves at medium energies including the Ore gap region using the close-coupling approximation with realistic wavefunctions for the following states: He(1s1s), He(1s2s), He(1s2p), He(1s3s), He(1s3p), Ps(ls), Ps(2s), Ps(2p). Calculations are reported of rearrangement cross sections to Ps(ls), Ps(2s) and Ps(2p) states for incident positron energies up to 200 eV. The present partial cross sections are in good agreement with experimental results and a variational calculation in the Ore gap region.